Near-field flame dynamics of liquid oxygen/kerosene bi-swirl injectors at supercritical conditions - Wang, Xingjian; Li, Yixing; Wang, Yanxing; Yang, Vigor (Combustion and flame, 2018)
The flame dynamics of liquid bi-swirl injectors are numerically investigated using the large eddy simulation technique. Liquid oxygen (LOX) and kerosene at subcritical temperatures are injected into a supercritical pressure environment. The theoretical framework is based on the full conservation laws and accommodates real-fluid thermodynamics and transport theories over the entire range of fluid states. Turbulence/chemistry interaction is modeled with a laminar flamelet library approach, the validity of which is demonstrated in the present work. The near-field flow and flame characteristics are carefully studied. The flame is anchored in the wake of the inner injector post by two counter-rotating vortices, and further stabilized by center and corner recirculation zones in the downstream region. Differences in the flow patterns between the cold-flow and combustion cases are recognized. Various geometric parameters, including recess region, post thickness, and kerosene annulus width, are examined in depth to explore their influence on flame characteristics. A recess region is found to be necessary to achieve efficient mixing and combustion. The absence of a recess region increases the penetration depth of the kerosene stream in the downstream region and reduces the thermal protection provided to the injector faceplate. On the other hand, a thicker LOX post or a wider kerosene annulus protects the faceplate more efficiently, and introduces larger recirculation zones near the LOX post surface and thus higher flow residence time to better anchor the flame. However, the flame attachment for thicker post and wider annulus induces a stronger heat flux to the post surface, and thus increases the risk of thermal failure of the injector device. The dynamic characteristics of the flame field are also discussed. The flow oscillations within the injector are found to be dominated by a quarter acoustic wave, while the oscillatory field near the injector exit is characterized by vortex shedding. The characteristic frequency of the vortex shedding is similar for different LOX post thicknesses and annulus widths, and is determined by the exit velocity profiles.